The economics and management of small business : an international perspective - Bannock, Graham (New York : Routledge, 2005)
The publication provides an international perspective on small businesses management including many pedagogical features such as questions for discussion, international case-studies, and empirical research.
Includes bibliographical references and index.
lje 15/01/14
Loans
Keywords: Small business; Small business -- Management; Small business -- Government policy; Economic development